Description of a new genus and five new species of tube-dwelling spider family Segestriidae (Araneae: Synspermiata) from Odisha, India - Choudhury, Sudhir Ranjan; Siliwal, Manju; Das, Sanjay Keshari; Giroti, André Marsola (Zootaxa, 2021)
The six-eyed spider family Segestriidae is poorly documented from India, with only five species belonging to two genera. Here we describe a new genus, Indoseges gen. nov. with five new spp. viz. I. malkhangiri sp. nov., I. sushildutta sp. nov., I. chilika sp. nov., I. narayani sp. nov. and I. satkosia sp. nov. from Odisha. The first two spp. are described based on both male and female specimens and the rest on females only. The new genus resembles the genus Ariadna Audouin, 1826; still, males differ with respect to first leg spines, shape and position of apophysis and in the palp structure, and females having distinct spination in palp tarsi and femur of first two legs, and in the genitalia structure. Along with a distribution map of the Segestriids of India this paper also provides natural history information about the new genus, a discussion on its relationship with Ariadna, and the putative synapomorphies that define its placement in the subfamily Ariadninae.